Vaccine-Hesitant Justifications - Nathan J. Rodriguez (SAGE Publishing, 2016)
Vaccine-preventable diseases have re-emerged as more individuals have strayed from the recommended inoculation schedule. Previous work on vaccine hesitancy is generally limited to content analyses. Using grounded theory, this project examines vaccine debates on a prominent discussion board over a period of five years. Individuals generally justified opposition or hesitancy toward vaccines through personal experience and/or research, and the concepts of narrative persuasion and the conflation of expertise help describe the most prominent characteristics of such discourse. A consideration of online comments regarding vaccinations allows practitioners to not only become better prepared for patient concerns they might encounter, and but also become more familiar with the types of anecdotes and narratives that may be influential but left unspoken in face-to-face conversations.